Philodemus, on anger - Philodemus, approximately 110 B.C.-approximately 40 B.C (Writings from the Greco-Roman world, 2020)
"This English translation of On Anger provides a newly read and supplemented Greek text of one of the most important "Herculaneum papyri," the only collection of literary texts to survive the eruption of Vesuvius in 79 CE. On Anger is our sole evidence for the Epicurean view of what constitutes natural and praiseworthy anger, as distinguished from unnatural pleasure in vengeance and cruelty for their own sake, a view that can be shown to have influenced Latin authors like Cicero, Horace and Virgil"--